HUBUNGAN SUMBER INFORMASI KESEHATAN REPRODUKSI DENGAN PERILAKU SEKSUAL PADA PELAJAR SMA NEGERI DI KOTA SABANG TAHUN 2015 - Safrida, Yuni Dewi; Silaban, Gerry; Ginting, Ns. Selamat (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2015)
Source of information obtained teenagers about reproduction health is pushed the behavior of the teenagers to know more about sexual problem. In line with the era of globalization, information and technology, there is a big change in the sexual behavior of teenagers. Unwanted pregnancy, unsafe abortions and an increase in cases of sexually transmitted infections, which is a problem in teenagers reproduction health in Indonesia. The results of research in the program of Muda Berkarya conducted by Yayasan Kita (2005), teenagers of Sabang and some other town in the province of Aceh are likely to be further involved in unsafe sexual behavior. The purpose of this survey study with cross sectional study design is to examine the relationship of reproduction health resources (role of media, role of parents, role of peers) on the sexual behavior of high school students in Sabang. The population of this study are 607 high school students and 113 of them were selected through univariate  proporsional hypothesis test to be the samples for this study and bivariate (Chi square test) with significance level α <0,05 and level of confidence of 95%. The results using Chi square test shows  that significant variables related to sexual behavior are: the role of the media (p = 0.018) role of parents (p = 0.043) and the role of peers (p = 0.014). All of these variables have been associated with sexual behavior. It is suggested that the Department of Health to improve the implementation of outreach programs Teenagers Reproduction Health. With the counseling of students to better understand and care for reproduction health. The Department of Education to improve reproductive health education curriculum, so that students are better able to keep the negative sexual behavior and pornography so that negative interactions can be avoided.